SUMMARY OF FOREST TYPOLOGY STUDIES IN RECENT YEARS. FOREST TYPOLOGY CLASSIFICATION OF CLIMATE - Migunova, E. S. (Forestry and Forest Melioration, 2018)
Studying for many years different problems of forest typology, we have solved such very complex issues as the assessment of the silvicultural characteristics of a large group of soils with symptoms of salinity. It was given not only the rationale, including quantitative characteristics of trophic status, which is the main argument at classification forest typology model but also it was revealed that this model is edaphic (soil and groundwater) grid systematizing forest habitats by the level of their fertility, nutrients, and moisture. It is also a perfect model of intrazonal diversity of nature in general, as the trophic scale of the grid is rigidly joined with the mineral composition of the surface sediments, which are the only source of mineral nutrients in the world for plants and humidity scale – with the relief of these sediments. According to our research, the composition and structure (relief) of the surface sediments is responsible for the diversity of vegetation and soil in a uniform climate in the region. These data define the output of forest typology to the level of natural science disciplines. It was also found out that in different areas intrazonal variety conforms the same regularities. This is revealed by the very regular changes in the composition and productivity of vegetation and fertility (productivity) of soil within the edaphic grid: from the most productive and diverse in composition of plant communities in the center of the grid on the richest at optimally humid lands, to the lowest productive at its corners – at poor, saline, dry and overmoistured lands. Location of the edaphic grid of individual regions in the global climate (geographical) grid creates a single classification model of all the major components of the environment, “periodic system” of unit ecosystem cells of nature. The coordinates of this edaphic(geo)-climate grid are the main abiotic factors – climate, surface sediments, and ground water, limiting life options – heat, moisture and nutrition, the dependent variables – biotic and bioinert – vegetation, animals, soil. Together they form an ecosystem (bio-ecosystem). This is a major scientific achievement of foresters, another breakthrough in the same natural-scientific level. V. V. Dokuchaev all his life urged to study nature as a whole, rather than individual its component parts, but he could not conceive of the possibility of creating a unified classification of nature. Summarizing the above-mentioned materials we especially emphasize that forest typology initially, since the formation, is not confined to the silvicultural and forestry problems. This is evidenced by the famous thesis of its founder G. F. Morozov “Forest is under the influence of the climate and the land power” and the thesis of A. A. Krudener on the first pages of his book: “Type of forest stand is the unity of climate, soils, and plant community”, i. e. the unity of the living and the environment. This thesis is the first definition of “ecosystem” in the history of science, and we don’t know better one. Also the first is designed by Krudener 100 years ago conjugate soil classification and forest stands dedicated to it. Such unity now is understood as an ecosystem. Exceptional is the principle of conjugation of different natural objects accepted by Krudener in his classification. Recognizing the full conditionality of vegetation from soils, the latter are classified not by their so-called “internal” properties – genetic type, a degree of humus content, structure etc., but by the growth of forest stands of different composition and productivity – oligotrophic or mesotrophic plants, xerophytes or hygrophytes. The boundaries of soil types are determined by the change of forest types as vegetation is recognized the criterion of soil quality. We call this technique “the key of Krudener”.